Effect of Vitamin D3 Fortification and Saskatoon Berry Syrup Addition on the Flavor Profile, Acceptability, and Antioxidant Properties of Rooibos Tea (Aspalathus linearis). Issue 3 (13th February 2017) - Grant, Jennifer; Ryland, Donna; Isaak, Cara K.; Prashar, Suvira; Siow, Yaw L.; Taylor, Carla G.; Aliani, Michel
Abstract: The unique characteristics and healthful reputation of caffeine‐free rooibos tea (RT) make it an ideal carrier for vitamin D3 supplementation, and a potential base for the addition of Saskatoon berry syrup (SBS), a natural flavor additive. The objective of this study was to determine the effect of vitamin D3 fortification and SBS addition on the flavor profile, consumer acceptability, and antioxidant properties of RT. Six formulations (RT, RT with SBS, RT with SBS and vitamin D3, RT with vitamin D3, green tea [GT], and GT with SBS) were evaluated by 12 trained panelists and 114 consumers. The formulations were also assessed for antioxidant capacity, physical characteristics, and untargeted phytochemical content. Sensory results revealed that the mean intensity values for berry and sweet attributes were significantly higher ( P < 0.05) while bitter and astringent attributes were significantly lower when SBS was added to RT samples compared to those without syrup. Acceptability of flavor, aftertaste, and overall acceptability were also significantly higher for the RT with SBS. The addition of SBS to RT significantly increased the antioxidant capacities which may increase the related health benefits of RT. SBS contributed several polyphenols, particularly flavonoids, to the tea. Vitamin D3 added to RT formulations did not significantly affect the sensory attributes, acceptability, or antioxidant content. For the development of a functional vitamin D3 fortified iced‐tea beverage that can be consumed as part of the daily diet, SBS could be a favorable flavoring additive that may provide additional health benefits.